Variation in seed dormancy of Chaco seasonally dry forest species: Effects of seed traits and population environmental conditions - Bertuzzi, Tania; Lopez Spahr, Diego; Gómez, Carlos Alberto; Sühring, Silvia Susana; Malagrina, Gisela Marina; Baskin, Carol C.; Galindez, Guadalupe (MDPI, 2023)
The persistence of subtropical seasonally dry forests urgently requires the implementation of ex situ conservation and restoration programs. We studied variation in seed traits and dormancy of six native species growing in seasonally dry Chaco forests of Argentina. We documented high intra- and interspecific variability in seed traits and dormancy. Fresh seeds of Geoffroea decorticans and Parasenegalia visco (Fabaceae) were water-permeable and nondormant (ND), while those of Parkinsonia praecox and Vachellia aroma (Fabaceae) were water-impermeable and had physical dormancy (PY). Seeds of Schnopsis lorentzii (Anacardiaceae) and Sarcomphalus mistol (Rhamnaceae) were water-permeable and had physiological dormancy (PD). Mechanical and chemical scarification were the most effective methods to break PY, and dry storage for 3 months was effective in breaking PD. Seeds of large-seeded species were ND or had PD, and those of small-seeded species had PY. Species inhabiting moist habitats had ND seeds, whereas those from seasonally dry habitats had seeds with PY or PD. These results suggest that seed traits and dormancy are species-specific and that intraspecific variation in seed traits is likely associated with high phenotypic plasticity of species in response to local environmental heterogeneity. These findings should be considered at the time of implementation of conservation techniques and for seed sourcing decisions for restoration.